PMMA characterization and optimization for Nano Structure formation - S Niza, Mohammad Bajuri; Nur Hamidah, Abdul Halim; Mohammad Nuzaihan, Md Nor; Uda, Hashim (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 18th - 19th May 2005 at Putra Palace Hotel, Kangar.